صناعة النوابض الفولاذية باستخدام الطاقة الحرارية للحقول الكهرومغناطيسية - بدور, جهاد; علي, عدنان (Latakia University Journal -Engineering Sciences Series, 2019)
تشغل النوابض دوراً مهماً في الكثير من أنواع الآلات والتجهيزات الميكانيكية والكهربائية وفي مختلف نواحي الحياة العملية. لتصنيع النوابض من الأسلاك الفولاذية بشكلها اللولبي لا بد من تسخينها، حيث استخدمت طرق تسخين يصدر عنها ملوثات كثيرة كالدخان، النفايات، والضجيج، لها أثرها السلبي في البيئة وصحة الإنسان. لذلك كان لابد من استخدام طريقة حديثة للتسخين، وهي الطاقة الحرارية للحقول الكهرومغناطيسية التي لا ينتج عنها أي دخان أو نفايات، وبالتالي يتم المحافظة على بيئة نظيفة مما ينعكس إيجابا على الإنسان. لتوليد هذه الحقول الكهرومغناطيسية تم تصميم ملف ذي شكل خاص غايته تمرير التيار الكهربائي اللازم لهذا الغرض ثم معرفة كيفية توزع الحقل بغية تحديد المنطقة التي يكون فيها التسخين منتظماً ومعرفة تأثير زاوية ميلان الملف على انتظام التسخين. Springs play an important role in all types of mechanical and electrical machines and equipment as well in all aspects of practical life. In order to manufacture springs, steel wires have to be heated. Many heating methods are used to produce different types of pollution such as smoke and noise. These polluted products have negative effects on the environment and human health. For this reason, there is a need for a new heating method like the thermal power of electromagnetic field that does not have any polluting waste. It maintains a clean environment positively reflecting on humans. For generating these electromagnetic fields, a special form of coil has been designed; its main purpose is to pass the proper electrical current, checking how the field is distributed for determining the area of uniform heating and examining the effect of the coil tilting angle on heating uniformity.